Analisis Manajemen Risiko Teknologi Informasi pada Website Ecofo Menggunakan ISO 31000 - Miftakhatun Miftakhatun (Journal of Computer Science and Engineering (JCSE), 2020)
The role of information technology in the current era is becoming large in aspects of life. One of them is in the State-Owned Enterprises (BUMN) in the East Banyumas KPH. The technology applied consists of a web-based information system that is used to manage ticket data designated by Ecofo. The application of technology is inseparable from the issuance of risks that arise that can hamper business processes. The purpose of this research is to study emerging issues and ways to save to minimize risks later on. This study uses the ISO 31000 method,which is a method that specifically discusses risk management,which has fivestages of communication and consultation, determining context, risk assessment, risk analysis, risk evaluation), risk use,and monitoring and review. The results of this study consist of documentation found that identified 24 risks that have threelevels of high risk, tenlevels of medium risk, and 11 levels of low risk that can be used as a reference to improve, manage and finance information technology assets in the future.